If p sin theta +q cos theta =a and p cos theta -q cos theta =b then p+a/q+b+q-b/p-a is equal to?
Answers
Answered by
19
Here is your answer in the attachment
Attachments:
![](https://hi-static.z-dn.net/files/dcc/6aecadd6ae173cd5539f884455147acc.jpg)
Answered by
20
Hi friends
Here is your answer
I
![a = p \: sin \alpha + q \: cos \alpha \\ {a}^{2} = {p}^{2} sin {}^{2} \alpha + {q}^{2} cos \alpha + 2pqsin \alpha \cos( \alpha ) a = p \: sin \alpha + q \: cos \alpha \\ {a}^{2} = {p}^{2} sin {}^{2} \alpha + {q}^{2} cos \alpha + 2pqsin \alpha \cos( \alpha )](https://tex.z-dn.net/?f=a+%3D+p+%5C%3A+sin+%5Calpha++%2B+q+%5C%3A+cos+%5Calpha++%5C%5C++%7Ba%7D%5E%7B2%7D++%3D++%7Bp%7D%5E%7B2%7D+sin+%7B%7D%5E%7B2%7D++%5Calpha++%2B++%7Bq%7D%5E%7B2%7D+cos+%5Calpha++%2B+2pqsin+%5Calpha++%5Ccos%28+%5Calpha+%29+)
II
![b = p \cos( \alpha ) - q \sin( \alpha ) \\ on \: squaring \\ {b}^{2} = {p}^{2} \cos {}^{2} ( \alpha ) + {q}^{2} \sin {}^{2} ( \alpha ) - 2pq \sin( \alpha ) \cos( \alpha ) b = p \cos( \alpha ) - q \sin( \alpha ) \\ on \: squaring \\ {b}^{2} = {p}^{2} \cos {}^{2} ( \alpha ) + {q}^{2} \sin {}^{2} ( \alpha ) - 2pq \sin( \alpha ) \cos( \alpha )](https://tex.z-dn.net/?f=b+%3D+p+%5Ccos%28+%5Calpha+%29++-+q+%5Csin%28+%5Calpha+%29++%5C%5C+on+%5C%3A+squaring+%5C%5C++%7Bb%7D%5E%7B2%7D++%3D++%7Bp%7D%5E%7B2%7D++%5Ccos+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++%2B++%7Bq%7D%5E%7B2%7D++%5Csin+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++-+2pq++%5Csin%28+%5Calpha+%29++%5Ccos%28+%5Calpha+%29+)
On Adding both equation
![{a}^{2} + {b}^{2} = {p}^{2} ( \sin {}^{2} ( \alpha ) + q {}^{2} \cos {}^{2} ( \alpha ) ) + {q}^{2} ( \sin {}^{2} ( \alpha ) + \cos {}^{2} ( \alpha ) ) \\ \\ {a}^{2} + {b}^{2} = {p}^{2} + {q}^{2} \\ as \: \sin {}^{2} ( \alpha ) + \cos {}^{2} ( \alpha ) = 1 {a}^{2} + {b}^{2} = {p}^{2} ( \sin {}^{2} ( \alpha ) + q {}^{2} \cos {}^{2} ( \alpha ) ) + {q}^{2} ( \sin {}^{2} ( \alpha ) + \cos {}^{2} ( \alpha ) ) \\ \\ {a}^{2} + {b}^{2} = {p}^{2} + {q}^{2} \\ as \: \sin {}^{2} ( \alpha ) + \cos {}^{2} ( \alpha ) = 1](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D++%2B++%7Bb%7D%5E%7B2%7D++%3D++%7Bp%7D%5E%7B2%7D+%28+%5Csin+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++%2B+q+%7B%7D%5E%7B2%7D+%5Ccos+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++%29+%2B++%7Bq%7D%5E%7B2%7D+%28+%5Csin+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++%2B++%5Ccos+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29+%29++%5C%5C++%5C%5C++%7Ba%7D%5E%7B2%7D++%2B++%7Bb%7D%5E%7B2%7D++%3D++%7Bp%7D%5E%7B2%7D++%2B++%7Bq%7D%5E%7B2%7D++%5C%5C+as+%5C%3A++%5Csin+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++%2B++%5Ccos+%7B%7D%5E%7B2%7D+%28+%5Calpha+%29++%3D+1)
Now we find the value
![\frac{p + a}{q + b} + \frac{q - b}{p - a} \\ \\ = \frac{ {p}^{2} - {a}^{2} + {q}^{2} - {b}^{2} }{(q + b)(p - a)} \\ \\ = \frac{ {a}^{2} + {b}^{2} - {a}^{2} - {b}^{2} }{(q + b)(p - a)} \\ \\ = 0 \frac{p + a}{q + b} + \frac{q - b}{p - a} \\ \\ = \frac{ {p}^{2} - {a}^{2} + {q}^{2} - {b}^{2} }{(q + b)(p - a)} \\ \\ = \frac{ {a}^{2} + {b}^{2} - {a}^{2} - {b}^{2} }{(q + b)(p - a)} \\ \\ = 0](https://tex.z-dn.net/?f=+%5Cfrac%7Bp+%2B+a%7D%7Bq+%2B+b%7D++%2B++%5Cfrac%7Bq+-+b%7D%7Bp+-+a%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B+%7Bp%7D%5E%7B2%7D++-++%7Ba%7D%5E%7B2%7D++%2B++%7Bq%7D%5E%7B2%7D+-++%7Bb%7D%5E%7B2%7D++%7D%7B%28q+%2B+b%29%28p+-+a%29%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B+%7Ba%7D%5E%7B2%7D++%2B++%7Bb%7D%5E%7B2%7D++-++%7Ba%7D%5E%7B2%7D+-++%7Bb%7D%5E%7B2%7D++%7D%7B%28q+%2B+b%29%28p+-+a%29%7D++%5C%5C++%5C%5C++%3D+0)
Hope it helps you
@ MSD
Here is your answer
I
II
On Adding both equation
Now we find the value
Hope it helps you
@ MSD
Similar questions
Social Sciences,
8 months ago
Math,
8 months ago
Math,
1 year ago
Environmental Sciences,
1 year ago